2006
DOI: 10.1590/s0101-31222006000200014
|View full text |Cite
|
Sign up to set email alerts
|

Adubação orgânica e mineral na produção de sementes de abobrinha

Abstract: Este estudo teve o objetivo de verificar os efeitos da adubação orgânica e mineral sobre os componentes do rendimento e potencial produtivo de sementes de Cucurbita pepo L. var melopepo cv. Caserta. A pesquisa foi conduzida no Centro Agrícola Demonstrativo da Prefeitura de Porto Alegre durante os anos de 2002/03. Os tratamentos consistiram em T1 = testemunha, T2 = adubação mineral e do T3 ao T6 em adubação orgânica (cama de aviário), nas doses de 63, 125, 187 e 250g.cova-1, respectivamente. O delineamento expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
2
2
1
6
Order By: Relevance
“…The number of ripe fruits per plant was not influenced by the doses of castor bean cake in topdressing or by the splittings, obtaining an average of 1.7 fruits. Rech, Franke and Barros (2006), studying organic and inorganic fertilization in the production of `Caserta` zucchini seeds, observed a significant effect on the number of fruits per plant, obtaining 1.2 fruits per plant in the control (dose 0), 1.3 with inorganic fertilization and 1.64 with the highest dose (250 g per pit) of poultry litter, which is lower than in the present study.…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…The number of ripe fruits per plant was not influenced by the doses of castor bean cake in topdressing or by the splittings, obtaining an average of 1.7 fruits. Rech, Franke and Barros (2006), studying organic and inorganic fertilization in the production of `Caserta` zucchini seeds, observed a significant effect on the number of fruits per plant, obtaining 1.2 fruits per plant in the control (dose 0), 1.3 with inorganic fertilization and 1.64 with the highest dose (250 g per pit) of poultry litter, which is lower than in the present study.…”
Section: Resultscontrasting
confidence: 82%
“…Satisfactory results with organic fertilization in several vegetables were also reported by other authors. Researching organic fertilization in the zucchini plantation, Rech, Franke and Barros (2006) reported increased fruit numbers and seed yield per plant as organic fertilizer doses were increased. Rocha et al (1998), studying melon, observed higher yields using 20 and 30 m 3 ha -1 of organic compost and 50% of the recommended mineral fertilization for the crop.…”
Section: Resultsmentioning
confidence: 99%
“…A utilização de adubação balanceada nutricionalmente é importantíssima nos campos de produção de sementes, por influenciar a produção e a qualidade, alterando características físicas, além de evitar o surgimento de anomalias no desenvolvimento das plântulas, tais ocorrências são resultantes das deficiências de minerais (RECH et al, 2006). O uso eficiente da água pelas culturas agrícolas depende, sobretudo, das condições físicas do solo, das condições atmosféricas, do estado nutricional das plantas, de fatores fisiológicos, da natureza genética e do seu estádio de desenvolvimento.…”
Section: Fundamentação Teóricaunclassified
“…Para qualquer cultura de hortaliça, a adubação orgânica e/ou química é indispensável para obter-se boa produtividade (RECH et al, 2006).…”
Section: Introductionunclassified